Fgf23 and parathyroid hormone signaling interact in kidney and bone. (15th November 2016) - Andrukhova, Olena; Streicher, Carmen; Zeitz, Ute; Erben, Reinhold G.
Abstract: Fibroblast growth factor-23 (FGF23) is a bone-derived hormone, suppressing renal phosphate reabsorption and vitamin D hormone synthesis in proximal tubules, and stimulating calcium reabsorption in distal tubules of the kidney. Here, we analyzed the long term sequelae of deficient Fgf23 signaling on bone and mineral metabolism in 9-month-old mice lacking both Fgf23 or Klotho and a functioning vitamin D receptor (VDR). To prevent hypocalcemia in VDR deficient mice, all mice were kept on a rescue diet enriched with calcium, phosphate, and lactose. VDR mutants were normocalcemic and normophosphatemic, and had normal tibial bone mineral density. Relative to VDR mutants, Fgf23/ VDR and Klotho/ VDR compound mutants were characterized by hypocalcemia, hyperphosphatemia, and very high serum parathyroid hormone (PTH). Despite ∼10-fold higher serum PTH levels in compound mutants, urinary excretion of phosphate and calcium as well as osteoclast numbers in bone remained unchanged relative to VDR mutants. The increase in plasma cAMP after hPTH(1–34) injection was similar in all genotypes. However, a 5-day infusion of hPTH(1–34) via osmotic minipumps resulted in reduced phosphorylation of extracellular signal-regulated kinase 1 and 2 (ERK1/2) in bone and kidney of Fgf23/ VDR and Klotho/ VDR compound mutants, relative to VDR and WT controls. Similarly, the PTH-mediated ERK1/2 phosphorylation was reduced in primary osteoblasts isolated from Fgf23 and Klotho deficient mice, but was restored by concomitant treatment with recombinant FGF23. Collectively, our data indicate that the phosphaturic, calcium-conserving, and bone resorption-stimulating actions of PTH are blunted by Fgf23 or Klotho deficiency. Hence, FGF23 may be an important modulator of PTH signaling in bone and kidney. Highlights: Aged Fgf23 and Klotho deficient mice develop severe secondary hyperparathyroidism. Fgf23 and Klotho deficient mice are characterized by renal and bony PTH resistance. Fgf23 signaling modulates the phosphaturic and calcium-saving renal actions of PTH. PTH-induced stimulation of bone resorption is blunted by lacking Fgf23 signaling.